2007
DOI: 10.1111/j.1365-2125.2007.03029.x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying how age and gender influence prescription drug use in a primary health care environment in Catalonia, Spain

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• Knowledge of prescription patterns in primary health care is an important tool in rational drug therapy.• Age and gender are the principal determining factors of cost variability between medical practices, due to drug prescriptions. • Age and gender are the principal determining factors of cost variability in relation to the therapeutic group. WHAT THIS STUDY ADDS• This study provides specific information on the use of drugs in the primary health care environment of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
63
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 28 publications
12
63
0
3
Order By: Relevance
“…This may be due to a combination of factors, such as worse perception of health and greater comorbidity among females, which leads to a higher frequency of medical visits and therefore a greater likelihood for diagnosis. 25,26 Medication use in the Spanish Roma community was found to increase gradually with age in both sexes. This was expected, as older individuals usually suffer from more diseases than younger individuals, and therefore use more prescribed medication.…”
Section: Discussionmentioning
confidence: 96%
“…This may be due to a combination of factors, such as worse perception of health and greater comorbidity among females, which leads to a higher frequency of medical visits and therefore a greater likelihood for diagnosis. 25,26 Medication use in the Spanish Roma community was found to increase gradually with age in both sexes. This was expected, as older individuals usually suffer from more diseases than younger individuals, and therefore use more prescribed medication.…”
Section: Discussionmentioning
confidence: 96%
“…One topic that has received attention is the possibility of gender bias in the provision of pain treatment. Although the use of both prescription and nonprescription analgesics is significantly higher among women than men,109,115,193 there is concern that women are at greater risk for undertreatment of pain 190. It has been observed that women presenting with chest pain are less likely than men to receive both invasive and noninvasive diagnostic and interventional cardiac procedures,80,339,369 though sex differences in symptom presentation and diagnostic test results may contribute to these disparities in management of chest pain 163,447.…”
Section: Sex Differences In Responses To Pain Treatmentmentioning
confidence: 99%
“…GPs' prescribing decisions have come under increased scrutiny, above all in those Italian regions where health care deficits remain high, and there is considerable pressure to contain costs by prescribing cost-effectively [8][9][10][11]. Thus, knowledge of prescription patterns is important in order to improve, evaluate and make adjustments to the pharmaceutical formulary [12].…”
Section: Introductionmentioning
confidence: 99%